Long-term impact of growth hormone therapy on mortality and type 2 diabetes in Prader–Willi syndrome: a nationwide cohort study - Choi, Yong Jun; Yang, Aram (Frontiers in Endocrinology, 2025)
BackgroundPrader–Willi syndrome (PWS) is a rare genetic disorder characterized by severe multisystem comorbidities and increased mortality. Although growth hormone therapy (GHT) is widely used as standard care, population-based evidence on its long-term safety, particularly in relation to mortality and type 2 diabetes mellitus (T2DM), remains limited. We aimed to investigate the associations between GHT duration, mortality, and T2DM incidence in PWS.MethodsThis is a nationwide cohort study using the Korean National Health Insurance Service database. A total of 385 individuals with PWS were identified between January 2005 and February 2023. GHT duration was the primary exposure. All-cause mortality was analyzed using Cox proportional hazards models, and T2DM risk was evaluated using multivariable logistic regression adjusted for age, comorbidities, and GHT duration.ResultsGHT duration did not directly impact mortality (OR 1.00, 95% CI: 0.99–1.00); however, peripheral vascular disease (aOR 10.66, 95% CI: 1.07–106.56), renal disease (aOR 17.45, 95% CI: 1.17–259.93), adrenal insufficiency (aOR 23.90, 95% CI: 3.19–178.34), and behavioral disorders (aOR 29.51, 95% CI: 2.64–329.95) were significant predictors of all-cause mortality. Longer GHT duration was independently associated with higher T2DM risk (aOR 1.06, 95% CI: 1.02–1.11). Older age, age at PWS diagnosis, and comorbidities (peptic ulcer disease, mild liver disease, and diabetes insipidus) were additional risk factors.ConclusionsGHT was not a direct predictor of mortality in PWS, which was instead influenced by comorbidities. However, its prolonged use was linked to increased T2DM. These findings support individualized risk assessment and metabolic monitoring in patients with PWS receiving GHT.